Analysis of the Pattern Marketing Channels and Marketing Margins Broiler in Tanggetada Village District Tanggetada Kolaka Regency - B. Bustang (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This study aims to determine the pattern of the marketing channel of Broiler and to find out how much the marketing margin and profit from the broiler marketing channel in Tanggetada Village, Tanggetada District, Kolaka Regency. This research was conducted in June 2019. The sample of this study was all the population. It is mean that many as two people who worked as breeders and retailers. This research uses quantitative and qualitative methods. The data analysis technique is descriptive and mathematical analysis. The results showed that only one pattern of broiler marketing channels: producers-retailers-consumers. The marketing margin of Broiler is IDR. 15,000/head, while the marketing profit of broiler IDR 11,380/ head.